#Baby Supplementary Food as Cyber Shield: Grounded Perspectives on Chinese Digital Feminism on RedNote - Liang, Meng; Zhang, Xiaoyue; Ye, Linqi (AoIR Selected Papers of Internet Research, 2026)
Chinese female users on RedNote have re-appropriated the #Baby Supplementary Food (#BSF) hashtag to evade male visibility and foster female-exclusive discourse. Originally intended for baby food content, #BSF now functions as a strategic shield against the male gaze, as parenting-related posts are considered less likely to appear in male-dominated feeds. This practice reflects a broader trend in China’s digital feminism, where women manipulate algorithmic affordances to create safer online spaces.This study investigates how #BSF facilitates a counterpublic sphere by examining 1,513 non-commercial posts. Using Python-based data mining and the official platform provided dataset, we filtered content to exclude genuine baby food posts and commercial promotions. We further use GSDMM topic modeling and critical discourse analysis (CDA) explored linguistic strategies used in #BSF-tagged posts.Our findings reveal that #BSF serves not only as a shield but also as a site of feminist resistance. Users build solidarity through intimate discourse and redefine traditional motherhood by positioning themselves as "babies" or "pet mothers," rejecting patriarchal maternal expectations. Through satire and self-infantilization, they subvert dominant gender norms and construct an alternative female-centered space.This study contributes to digital feminism by demonstrating how Chinese women leverage platform affordances to resist online male dominance. It also introduces a systematic methodological approach to studying hashtag-based expression and counter publics making on Chinese social media platforms.